THE INDONESIAN NAVY’S ACTIVITIES TO SECURE THE NORTH NATUNA SEA FROM THE PESPECTIVE OF THE NAVY’S TRINITY ROLES (2014 - 2019) - Vania Lalita; Anak Agung Banyu Perwita (The Republic of Indonesia Defense University, 2020)
This article aims to explicate the role and activities of the Indonesian Navy to protect Indonesia's sovereignty in the North Natuna Sea based on the perspective of the Naval Trinity Theory. To do so, this paper combines the application of some pertinent concepts and theories, such as maritime security theory, maritime diplomacy, and the Navy trinity roles of Ken Booth. It shows that those pertinent concepts and theories are very essential to further understand the roles and activities of the Indonesian Navy to protect our sovereignty in the North Natuna Sea. This paper utilizes the method of descriptive qualitative research by looking at the activities of the Indonesian Navy's to Secure North Natuna Sea from the perspective of the Navy’s Trinity Roles (2014 - 2019).